(untitled) (World Economics and Finance Bulletin, 2024)
The main objective of the research study is to try to discover the impact of applying blockchain technology on improving audit quality in Iraq To this end, the researcher relied on a questionnaire distributed to external auditors and faculty, The research found a moral impact between the use of blockchain technology on the quality of the audit process digital blockchains provide transparency and data privacy, increasing objectivity when the auditor relies on data, Providing evidence of relative importance to the element under scrutiny increases the auditor’s persuasion as well as fast access to data and easy retrieval by the auditor, In addition to the possibility of continuous auditing, and finally supporting the independence of the auditor where under digital block chains there is no need for management reports, Because the auditor and management are members of the network, the research recommends that the chains of blocks should be adopted by large sectors such as banks and Iraqi government entities for business development .